The Role of Information Sources in Firm R&D Activities - The Case of German Knowledge Intensive Industries - Prokop, Viktor; Stejskal, Jan; Hájek, Petr (Kaunas University of Technology, 2019)
R&D activities affect the ability to create innovation for every firm. Many studies have shown that R&D activities are influenced by a number of determinants and the environment (R&D milieu) in which individual economic entities exist. Due to the nature of firms' production, it is important to note that not every firm needs the same amount of information and knowledge. This study will also affect the efficiency of the use of information sources in R&D activities. In practice, it is necessary to know the dependence of companies and their R&D activities on the available information sources so that public policy makers can better target public policy and possible financial support schemes (grant schemes), because, the one size-fits all principle cannot be assumed. Therefore, the aim of this paper is to analyze the role of information resources in the knowledge intensive industries in the largest EU economy in terms of GDP, i.e. Germany. For the analysis, Eurostat CIS data and own regression model were used. The results show that the knowledge environment has a major impact on the development of R&D in the German knowledge intensive firms. German companies sourced information from the market (especially clients and customers), and all firms acquired information and knowledge from collaborating with universities. The biggest impetus for the realization of R&D activities is for firms to focus on markets outside the EU.
Role informačních zdrojů v podnikových výzkumných a vývojových činnostech - případ německých průmyslových odvětví intenzivních znalostí
Keywords: information sources; knowledge; knowledge intensive industry; germany